Epidural anesthesia for repeat cesarean delivery in a parturient with Klippel-Feil syndrome - Kathleen A Smith; Adrienne P Ray (Wolters Kluwer Medknow Publications, 2011)
A patient with Klippel-Feil syndrome, morbid obesity, and scoliosis required cesarean delivery. Her previous cesarean deliveries were performed under general anesthesia. She desired a regional technique. Following aspiration prophylaxis and placement of standard monitors, ultrasound was used to identify midline and L 2-3 interspace. Unintentional dural puncture occurred at 10 cm, with an inability to advance the catheter. On second attempt, an epidural catheter was placed easily. After negative test dose, 18 ml of 2% lidocaine with epinephrine was administered to the patient. A T4 level was achieved. The patient tolerated surgery well. Complete block resolution occurred at 4 hours with no neurologic sequelae.